2016
DOI: 10.3892/or.2016.5001
|View full text |Cite
|
Sign up to set email alerts
|

PIN1 in hepatocellular carcinoma is associated with TP53 gene status

Abstract: Phosphorylation of proteins on serine/threonine residues that precede proline (pSer/Thr-Pro) is specifically catalyzed by the peptidyl-prolyl cis-trans isomerase PIN1. PIN1-mediated prolyl-isomerization induces cell cycle arrest and growth inhibition through the regulation of target proteins, including TP53. We examined whether PIN1 acts in a different manner according to TP53 gene status in hepatocellular carcinoma (HCC). We investigated the expression of PIN1 and TP53 proteins in 119 HCC tissue samples. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Interestingly, a number of studies indicated that Pin1 increases p53-induced cell senescence and apoptosis 88 , 89 . However, Pin1 expression is higher in HCC cells with mutant p53 (p53M) compared to wild-type p53 (p53WT), and the deletion of Pin1 significantly reduces the proliferation of p53M HCC cells but not p53WT 90 . More research revealed that Pin1 facilitates the p53M-induced aggressiveness of cancers 33 , 91 , 92 , which contributes to a reasonable explanation for why p53 is aberrant in most cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a number of studies indicated that Pin1 increases p53-induced cell senescence and apoptosis 88 , 89 . However, Pin1 expression is higher in HCC cells with mutant p53 (p53M) compared to wild-type p53 (p53WT), and the deletion of Pin1 significantly reduces the proliferation of p53M HCC cells but not p53WT 90 . More research revealed that Pin1 facilitates the p53M-induced aggressiveness of cancers 33 , 91 , 92 , which contributes to a reasonable explanation for why p53 is aberrant in most cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Pin1 is overexpressed in about 70% of human HCC patients and it promotes heptocarcinogenesis in cell line PLC/PRF/538394041. Pin1 might play different roles in HCC cells depending on status of TP53 gene mutation42. Pin1 single nucleotide promoter and exon polymorphisms are associated with the susceptibility of HBV-related HCC43.…”
mentioning
confidence: 99%
“…We focused our attention in the ones whose levels changed upon LPS challenge and were then restored after 4-PBA treatment, and we identified 12 proteins that followed this pattern (Figure 5C-O). Levels of six of these proteins dropped with LPS and returned to normal values after 4-PBA treatment (Figure 5D-I): Pin1 (a peptidyl isomerase with a role in regulation of TP53, stress and cytokine signaling in immune system) 63 , Gpm6a, Ephx2, L2hgdh, Dhdh (general metabolic modulators) and Tmed5 (Transmembrane P24 Trafficking protein 5 involved in ER-Golgi trafficking and WNT signaling) 64 . The other six proteins had elevated levels upon LPS challenge and returned to low levels with 4-PBA (Fig.…”
Section: Resultsmentioning
confidence: 99%